Penggunaan Aplikasi Pln Mobile Sebagai Sarana Komunikasi Digital dalam Upaya Meningkatkan Kualitas Pelayanan Pelanggan Pt Pln (Persero) Up3 Balikpapan - Asad Amaluddin Haq (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Every customer of PT PLN (Persero) is entitled to good service, PT PLN (Persero) has a responsibility to the reliability of electricity supply of its customers. Efforts to maintain and improve the reliability of electricity supply is a form of seriousness in implementing excellent service to improve customer satisfaction. Digital communication can speed up information between the fault service officer and the customer and affect the increase in customer satisfaction. The phenomenon that occurs in relation to digital communication related to customer service is the use of applications that can be accessed using the smartphone of each customer and fault service officer. Services can be done anywhere, anytime and anyone as long as they are connected to an internet connection.